Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

Capacitance-voltage spectroscopy on InAs quantum dot valence band states in tilted magnetic fields - Reuter, Dirk; Roescu, R; Zeitler, U; Maan, J C; Wieck, A D (Journal of Physics: Conference Series)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Holistic Model-Based Testing for Business Information Systems - Mlynarski, Michael (Proceedings of 3rd International Conference on Software Testing, Verification and Validation)

A Generic Meta-Model-based Approach for Specifying Framework Functionality and Usage - Christ, Fabian; Bals, Jan-Christopher; Engels, Gregor; Gerth, Christian; Luckey, Markus (Proceedings of the 48th International Conference on Objects, Models, Components and Patterns (TOOLS'10), Málaga (Spain))

Graph Transformations and Model-Driven Engineering: The Merits of Manfred Nagl - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm; Schürr, Andy; Westfechtel, Bernhard (Graph Transformations and Model-Driven Engineering)

Knowledge Transfer in Global Software Development - Leveraging Acceptance Test Case Specifications - Engels, Gregor; Salger, Frank (In Proceedings of the ACM/IEEE 32nd International Conference on Software Engineering (ICSE), New Ideas and Emergent Results program, May 2010, Cape Town (South Africa))

Proceedings 12. Workshop Software-Reengineering (WSR) & 2. Workshop Design for Future 2010 (DFF) - Gimnich, Rainer; Kaiser, Uwe; Momm, Christof; Quante, Jochen; Riediger, Volker; Sauer, Stefan; Trifu, Mircea; Winter, Andreas

Precise Detection of Conflicting Change Operations using Process Model Terms - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Proceedings of the ACM/IEEE 13th International Conference on Model Driven Engineering Languages and Systems (MODELS'10))
Version management of process models requires that changes can be resolved by applying change operations. Conflict detection is an important part of version management and the minimization of the number of detected conflicts also reduces the overhead when resolving changes. As not every syntactic conflict leads to a conflict when taking into account model semantics, a computation of conflicts solely on the syntax leads to an unnecessary high number of conflicts. In this paper, we introduce the notion of syntactic and semantic conflicts for change operations of process models. We provide a method how to efficiently compute conflicts, using a term formalization of process models. Using this approach, we can significantly reduce the number of overall conflicts and thereby reduce the amount of work for the user when resolving conflicts.

Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 7th International Conference on Services Computing (SCC'10))

Enriching RUP with key success factors for large-scale custom software development projects - Heinemann, Marianne; Duwe, Bettina; Engels, Gregor (Software & Systems Engineering Essentials (SEE) 2010)

Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Engels, Gregor (Integration von Vorgehensmodellen und Projektmanagement)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kinder und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Dynamic Computation of Change Operations in Version Management of Business Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 6th European Conference on Modelling Foundations and Applications (ECMFA'10))
Version management of business process models requires that changes can be resolved by applying change operations. In order to give a user maximal freedom concerning the application order of change operations, position parameters of change operations must be computed dynamically during change resolution. In such an approach, change operations with computed position parameters must be applicable on the model and dependencies and conflicts of change operations must be taken into account because otherwise invalid models can be constructed. In this paper, we study the concept of partially specified change operations where parameters are computed dynamically. We provide a formalization for partially specified change operations using graph transformation and provide a concept for their applicability. Based on this, we study potential dependencies and conflicts of change operations and show how these can be taken into account within change resolution. Using our approach, a user can resolve changes of business process models without being unnecessarily restricted to a certain order.

A Meta-Method for Defining Software Engineering Methods - Engels, Gregor; Sauer, Stefan (Graph Transformations and Model-Driven Engineering)

Erweiterung des TPI-Modells zur Reifegradbewertung unter Berücksichtigung von projekteigenen Anforderungen - Sancar, Yavuz; Schumacher, Claudia (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Assessments in Global Software Development: A Tailorable Framework for Industrial Projects - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings ACM/IEEE 32nd International Conference on Software Engineering, Software Engineering in Practice Track, Cape Town, South Africa (ICSE'10))

SheetDiff: A Tool for Identifying Changes in Spreadsheets - Chambers, Chris; Erwig, Martin; Luckey, Markus (Proceedings of the 26th IEEE Symposium on Visual Languages and Human-Centric Computing 2010 (VL/HCC 2010))

Model-driven Development of Advanced User Interfaces - Van den Bergh, Jan; Meixner, Gerrit; Breiner, Kai; Pleuß, Andreas; Sauer, Stefan; Hussmann, Heinrich (Proc. 28th International Conference on Human Factors in Computing Systems (CHI 2010))

Transfer of Testing Research from University to Industry: An Experience Report - Güldali, Baris; Sauer, Stefan (online Proc. of International TestIstanbul Conference 2010 (URL: www.testistanbul.org/presentations.html))
Software Quality Lab (s-lab) is an open multi-private-public partnership institute for knowledge and technology transfer. In s-lab, partners from industrial software development closely cooperate with research groups of the University of Paderborn. Together with partners from industry, s-lab develops and evaluates constructive and analytical methods and tools of software engineering for obtaining high-quality software. Testing plays an important role in analytical quality assurance within s-lab’s activities. Thereby our main focus lies on the development of testing methods, test automation tools and test management concepts for the individual needs of the industrial partners. Because of the different requirements of the university and the industry; the cooperation involves some challenges, e.g. defining projects aiming at the commercial interests of the industry and addressing interesting research questions. In this paper, we give an overview of testing activities in s-lab and address targets and challenges of the cooperative work between industry and university. We also summarize the lessons learned during the numerous testing projects especially in the domain of business information systems.

Verteiltes Testen heterogener Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Software Engineering 2010 (SE2010))

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Expected interference in wireless networks with geometric path loss: a closed-form approximation - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger (IEEE Communications Letters)

Automated Development of Cooperative MAC Protocols - A Compiler-Assisted Approach - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger (Mobile Networks and Applications)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Risk Aware Overbooking for Commercial Grids - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing - 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor
Modern business process modeling environments support distributed development by means of model version control, i.e., comparison and merging of two different model versions. This is a challenging task since most modeling languages support an almost arbitrary creation of process models. Thus, in multi-developer environments, process models or parts of them are often syntactically very different but semantically equivalent. Hence, the comparison of business process models must be performed on a semantic level rather then on a syntactic level. For the domain of business process modeling, this problem is yet unsolved. This paper describes an approach that allows the semantic comparison of different business process models using a normal form. For that purpose, the process models are fully automatically translated into process model terms and normalized using a term rewriting system. The resulting normal forms can be efficiently compared. Our approach enables the semantic comparison of business process models ignoring syntactic redundancies.

Full Semantics Preservation in Model Transformation - A Comparison of Proof Techniques - Hülsbusch, Mathias; König, Barbara; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike

Applying heuristic methods for job scheduling in storage markets - Finkbeiner, Josef; Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In double-sided markets for computing resources an optimal allocation schedule among job offers and requests subject to relevant capacity constraints can be determined. With increasing storage demands and emerging storage services the question how to schedule storage jobs becomes more and more interesting. Since such scheduling problems are often in the class NP-complete an exact computation is not feasible in practice. On the other hand an approximation to the optimal solution can easily be found by means of using heuristics. The problem with this attempt is that the suggested solution may not be exactly optimal and is thus less satisfying. Considering the two above mentioned solution approaches one can clearly find a trade-off between the optimality of the solution and the efficiency to get to a solution at all. This work proposes to apply and combine heuristics in optimization to gain from both of their benefits while reducing the problematic aspects. Following this method it is assumed to get closer to the optimal solution in a shorter time compared to a full optimization.
Keywords: Decision Support System; Algorithms; Optimization; Market Engineering

From "Take-it-or-leave-it" offers to "Take-it-or-be-left-out" Ultimatum - A trade mechanism for Online Services - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In a world, where more and more businesses seem to trade in an online market, the supply of online services to supply the ever-growing demand could quickly reach its capacity limits. Online service providers may find themselves maxed out at peak operation levels during high-traffic timeslots but too little demand during low-traffic timeslots, although the latter is becoming less frequent. At this point not only deciding which user is allocated what level of service becomes essential, but also the magnitude of the service provided, can be controlled by pricing. Pricing is an important factor when efficient and acceptable allocation of resources between individuals must be reached. Without prices, transferring or sharing goods would be impossible. In sharing information, pricing a product however is not as simple as relatively pricing an apple or a pear. Often the costs, and hence the prices are simply unknown. Backed by this scenario, the online services market could be combined with the market design mechanism of diamonds. For this we propose an ultimatum pricing strategy which effectively allows for valuations to be accounted for, but no longer a necessity when pricing in grid, cloud or other online computing environments.
Keywords: Posted Price; Ultimatum Game; Energy Efficiency; Mechanism Design

Geschäftsmodelle in virtuellen Spielwelten

Erfolgsfaktoren von Testprozessbewertungsmodellen - Brüseke, Frank; Sancar, Yavuz; Yigitbas, Enes (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Editorial: Aufschwung mitgestalten - Kabst, Rüdiger

HR Business Partner gesucht - Kabst, Rüdiger; Kötter, P M; Meifert, M; Wehner, M C

Editorial: Verdrängte Herausforderung Demographie - Kabst, Rüdiger

Was High-Performer besser machen: Was unterscheidet erfolgreiche von weniger erfolgreichen Unternehmen beim Employer Branding? - Kabst, Rüdiger; Baum, M; Fortange, A

Interim Management: Auf dem Weg zur Selbstverständlichkeit - Kabst, Rüdiger

A Conceptual Framework for the International Staffing of Early Internationalizers - Isidor, R; Schwens, C; Kabst, Rüdiger (Internationale Unternehmungen und das Management ausländischer Tochtergesellschaften)

Growth and Internationalization of Renewable Energy and New Technology-Based Firms - Schwens, C; Steinmetz, Holger; Kabst, Rüdiger (Innovation and International Corporate Growth)

Institutionalisierung der Personalentwicklung: Ist der Patient auf dem Weg der Besserung? - Kabst, Rüdiger; Wehner, M C (Strategische Personalentwicklung)

Personalmanagement der Zukunft: Quo Vadis? - Kabst, Rüdiger; Wehner, M C (Jahrbuch Personalentwicklung 2010)

Vertrauen, Opportunismus, Kontrolle: Eine empirische Analyse von Joint Venture Beziehungen vor dem Hintergrund der Transaktionskostentheorie. - Eberl, P; Kabst, R (Management von Netzwerkorganisationen)

Enlarging the focus on the role of competencies, abilities, and personality in management research. - Kabst, Rüdiger; Isidor, R; Steinmetz, Holger; Schwens, C (Management Revue: The International Review of Management Studies.)

Management accountants as business partners: An empirical analysis based on the theory of reasoned action - Wolf, S; Weißenberger, B E; Barbara, E; Kabst, Rüdiger; Wehner, M

Are networks always beneficial? An empirical analysis on the relationship between knowledge intensity and international new venturing - Baum, M; Schwens, C; Kabst, Rüdiger

Der Einfluss des Geschlechts auf die Gründungsintention – Ein meta-analytisches Pfadmodell (The influence of gender on entrepreneurial intention – a meta-analytical path model) - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger

Different types of international new ventures: A latent class analysis - Baum, M; Schwens, C; Kabst, Rüdiger

The different types of international new ventures: A latent class analysis - Baum, M; Schwens, C; Kabst, Rüdiger

The impact of employer awards on employer knowledge and applicant attraction: The moderating influence of corporate brand awareness - Baum, M; Kabst, Rüdiger

,,Blended Professionals´´ als Akteure einer institutionsweiten Hochschulentwicklung - Jenert, Tobias; Brahm, Taiga (Zeitschrift für Hochschulentwicklung)
Die aktuelle hochschuldidaktische Diskussion ist durch Schlüsselbegriffe wie Outcome- und Kompetenzorientierung geprägt. Allerdings sind die Strategien zur nachhaltigen Gestaltung der Lehr- und Lernpraxis bisher nur wenig differenziert. Der Beitrag stellt das Konzept einer "institutionsweiten Hochschulentwicklung" vor. Dieses spricht individuelles Handeln von Lehrenden und Lernenden sowie curriculare und organisationale Aspekte an. Mittels Experteninterviews wird gezeigt, dass Hochschulentwicklung eine "Third-Space-Funktion" zwischen Akademie und Administration einnimmt. Das personelle Profil solcher Einrichtungen verlangt nach "Blended Professionals", die sowohl als Servicepersonal als auch als Mitglieder der akademischen Welt wirkungsvoll agieren können.
Keywords: Hochschulentwicklung; educational development; higher education; Hochschuldidaktik

Zugänge zum Begriff der Lernkultur: Eine Systematisierung auf Basis kultur-und lerntheoretischer Überlegungen - Jenert, Tobias; Gebhardt, Anja
"Lernkultur" wird als Begriff häufig gebraucht und fast ebenso häufig definiert  das gilt für den betrieblichen Kontext ebenso wie für die Bereiche der Schul-, Hochschul-, Berufs- und Erwachsenenbildung (z. B. Wulf, Althans, Blaschke, Ferrin, Göhlich, Jörissen, Mattig et al., 2007; Jenert, Zellweger Moser, Dommen & Gebhardt, 2009; Kirchhöfer, 2004; Erpenbeck & Sauer, 2000). Trotz der grossen Aufmerksamkeit, die der Begriff in den letzten zwei Jahrzehnten erfahren hat, kann man nicht von einem in sich geschlossenen Forschungsprogramm sprechen. Die Zugänge zum Phänomenbereich Lernkultur sind ebenso vielfältig wie die hinter einzelnen Ansätzen stehenden Lernkulturkonstrukte. Den Autoren ist keine Publikation bekannt, welche unterschiedliche Ansätze der Lernkulturforschung systematisch aufarbeitet. Eine wichtige Referenzquelle ist der Bericht von Kuh und Whitt (1988) "The Invisible Tapestry: Culture in American Colleges and Universities". Ausgehend von einer fundierten Übersicht zu unterschiedlichen Zugängen zum Kulturbegriff (oft in starker Anlehnung an die Organisationskulturforschung (vgl. Allaire & Firsirotu, 1984)) stellen die Autoren ein Rahmenmodell zur Analyse von Hochschulkulturen vor (Kuh und Whitt, 1988, S. 56). Diese Arbeit erweist sich für ein besseres Verständnis unter-schiedlicher Zugänge zum Lernkulturbegriff als aufschlussreich, weil im Kontext Hoch-schule zwangsweise viele Aspekte des Lernens und Lehrens angesprochen werden. Allerdings fokussiert auch dieser Bericht nicht das Konstrukt der Lernkultur und bietet damit nur einen Ausgangspunkt für die Identifizierung unterschiedlicher Zugänge.
Keywords: Lernkultur; learning culture; culture theory; approaches to learning culture; culture of learning

Hochschulentwicklung als Gestaltung von Lehr-und Lernkultur: eine institutionsweite Herangehensweise an lehrbezogene Veränderungsprojekte an Hochschulen - Brahm, Taiga; Jenert, Tobias; Meier, Christoph
Keywords: Lernkultur; Hochschulentwickung; Hochschuldidaktik; Hochschullehre; HEI development

Learning Cultures at Higher Education Institutions: Outlining a wohle-institution approach to teaching and learning - Jenert, Tobias; Gebhardt, Anja
Keywords: earning culture; Lernkultur; whole-institution approach; higher education; Hochschule

Cultural Explorations: How Socio-material Contexts Influence Knowledge Interaction - Jenert, Tobias (Beyond Knowledge Management)

Oxygen sensing by fluorescence quenching of [Cu(btmgp)I] - Herres-Pawlis, Sonja; Berth, Gerhard; Wiedemeier, Volker; Schmidt, Ludger; Zrenner, Artur; Warnecke, Hans-Joachim (Journal of Luminescence)
A fluorescence study of acetonitrile solutions of bis(tetramethylguanidine)propane, copper(I)-iodide and [Cu(btmgp)I] was performed and the chemical reaction of the latter species with O2 was investigated at room temperature. The actual quenching process via O2 gassing was studied and an exponential dependence of the fluorescence intensity with respect to the complex concentration was observed. Furthermore the survey was deepened on time resolved fluorescence properties of solved [Cu(btmgp)I] in a wider concentration range. The applicability of this complex for O2 sensing inside a microreactor system was proven by confocal fluorescence measurements. It was shown that the investigated system can be used for oxygen sensing in the copper concentration range from 10−2 to 10−9 mol/l.
Keywords: Copper Oxygen Fluorescence quenching N donor ligands

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Resonant photocurrent-spectroscopy of individual CdSe quantum dots - Panfilova, M.; Michaelis de Vasconcellos, S.; Pawlis, A.; Lischka, K.; Zrenner, Artur (Physica E: Low-dimensional Systems and Nanostructures)
Here we report on investigations on CdSe quantum dots incorporated in ZnSe based Schottky photodiodes with near-field shadow masks. Photoluminescence and photocurrent of individual quantum dots were studied as a function of the applied bias voltage. The exciton energy of the quantum dot ground state transition was shifted to the excitation energy by using the Stark effect tuning via an external bias voltage. Under the condition of resonance with the laser excitation energy we observed a resonant photocurrent signal due to the tunnelling of carriers out of the quantum dots at electric fields above 500 kV/cm.
Keywords: CdSe/ZnSe quantum dots; Photodiode; Quantum confined Stark Effect; Photocurrent; II–VI Semiconductors

An empirical examination of the contribution of capabilities to the competitiveness of logistics service providers - Liu, Xiaohong; Grant, David B.; McKinnon, Alan C.; Feng, Yuanhua (International Journal of Physical Distribution & Logistics Management)

Sources of competitiveness for logistics service providers: a UK industry perspective - Liu, Xiaohong; McKinnon, Alan C.; Grant, David B.; Feng, Yuanhua (Logistics Research)

Managing customer share in key supplier relationships - Eggert, Andreas; Ulaga, Wolfgang (Industrial Marketing Management)

Creating and appropriating value in collaborative relationships - Wagner, Stephan M; Eggert, Andreas; Lindemann, Eckhard (Journal of business research)

Kundenbindung auf Basis des Relationship Value - Eggert, Andreas; Garnefeld, Ina (Handbuch Kundenbindungsmanagement)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten

Extremely low-loss slow-light modes in plasmonic dielectric hybrid systems - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Semiconductor plasmon laser - Sorger, Volker J.; Oulton, Rupert F.; Zentgraf, Thomas; Ma, Renmin; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Individuelle Bildungsgänge im Berufsbildungssystem - Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Towards Model-based Acceptance Testing for Scrum - Löffler, Renate; Güldali, Baris; Geisen, Silke (Softwaretechnik-Trends)

Starthilfe für modellbasiertes Testen - Güldali, Baris; Jungmayr, Stefan; Mlynarski, Michael; Neumann, Stefan; Winter, Mario (OBJEKTspektrum)

Tabellarischer Vergleich der Prozessmodelle für modellbasiertes Testen aus Managementsicht - Beulen, Dominik; Güldali, Baris; Mlynarski, Michael (Softwaretechnik-Trends)

Agiles Testen in Großprojekten mit TDD und Testaspekten: Beobachtungen und erste Erfahrungen - Späth, Melanie; Mlynarski, Michael (Softwaretechnik-Trends)

Automated acceptance testing tools for web applications using Test-Driven Development - Jureczko, Marian; Mlynarski, Michael (Electrical Review)
In the last years the software engineering community pays a strong interest in agile development methods. Those methods place software testing for example the Test-Driven Development method as an important task of the development process. Agile projects rely on good test automation tools. In this paper we evaluate five test automation tools for their usage in acceptance testing for web applications using Test-Driven Development.

Rollenbasierte Kompetenzbilanz - Potenziale und Herausforderungen für das berufsschulische Übergangssystem - Frehe, Petra; Kremer, H.-Hugo (Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich)

Controlled Etching Behavior of O-Polar and Zn-Polar ZnO Single Crystals - Mehta, M.; Meier, Cedrik (Journal of The Electrochemical Society)

Electroluminescence from silicon nanoparticles fabricated from the gas phase - Theis, Jens; Geller, Martin; Lorke, Axel; Wiggers, Hartmut; Wieck, Andreas; Meier, Cedrik (Nanotechnology)

Model-Based Software Product Lines Testing Survey - Oster, Sebastian; Wübbeke, Andreas; Engels, Gregor; Schürr, Andy (Model-Based Testing For Embedded Systems)

Variabilitätsmanagement in Anforderungs- und Testfallspezifikation für Software-Produktlinien - Wübbeke, Andreas
Software Product Lines (SPL) are a development paradigm allowing the reduction of the software system development time while increasing their quality. To reach these goals, the artefacts being part of many or all software systems are developed only once and reused within the different software systems. The software systems developed by a software product line approach are called products. Like a thread the reuse of artefacts is woven into the software product line development process. As some artefacts are only used for the development of some products, these artefacts constitute the variability of the SPL. First of all, the modelling of variability has to be enabled in every artefact. Beside this, dependencies can arise between variable artefacts. The modelling of variability and dependencies also demands the redevelopment or adaption of specification techniques for these artefacts. This thesis focuses on the variability management concerning requirements and test case specification for Software Product Lines. For this purpose, existing modelling languages and specification techniques are augmented with variability instead of redeveloping similar software development artefacts over and over again. In order to augment the modelling languages by variability, a language construction process based on a meta model of the variability management is defined. In order to manage the dependencies between variable artefacts, a feature based variability management is introduced. Finally, the extension of specification techniques for requirements specifications based on use case descriptions and test specifications are described. The contribution of this thesis is substantiated by a prototypical tool support and an industrial case study.

Test-driven Language Derivation with Graph Transformation-based Dynamic Meta Modeling - Engels, Gregor; Soltenborn, Christian (Proceedings of the International Colloquium on Graph and Model Transformation (GraMoT 2010), Berlin (Germany))
Deriving a new language L_B from an already existing one L_A is a typical task in domain-specific language engineering. Here, besides adjusting L_A's syntax, the language engineer has to modify the semantics of L_A to derive L_B's semantics. Particularly, in case of behavioral modeling languages, this is a difficult and error-prone task, as changing the behavior of language elements or adding behavior for new elements might have undesired side effects. Therefore, we propose a test-driven language derivation process. In a first step, the language engineer creates example models containing the changed or newly added elements in different contexts. For each of these models, the language engineer also precisely describes the expected behavior. In a second step, each example model and its description of behavior is transformed into an executable test case. Finally, these test cases are used when deriving the actual semantics of L_B - at any time, the language engineer can run the tests to verify whether the changes he performed on L_A's semantics indeed produce the desired behavior. In this paper, we illustrate the approach using our graph transformation-based semantics specification technique Dynamic Meta Modeling. This is once more an example where the graph transformation approach shows its strengths and appropriateness to support software engineering tasks as, e.g., model transformations, software specifications, or tool development.

Agility vs. Model-based Testing: A fair Play? - Güldali, Baris; Mlynarski, Michael (Proceedings of the IWK2010 Workshops: The First International Workshop on Evolution Support for Model-Based Development and Testing (EMDT2010))

Verknüpfung von kombinatorischem Plattform- und individuellem Produkt-Test für Software-Produktlinien - Wübbeke, Andreas; Oster, Sebastian (Proceedings of Produktlinien im Kontext (PIK2010))

Towards Economical Software Release Recommendations - Sancar, Yavuz; Brüseke, Frank; Voigt, Hendrik; Sauer, Stefan; Engels, Gregor (ECOOP 2010 - Workshop on Testing Object-Oriented Software Systems (ETOOS))

A Framework for Change Management of Business Process Models - Gerth, Christian (Proceedings of the Joint Workshop of the German Research Training Groups in Computer Science)

Reusing Security Requirements using an Extended Quality Model - Luckey, Markus; Baumann, Andrea; Méndez Fernández, Daniel; Wagner, Stefan (Software Engineering for Secure Systems, 2010. SESS '10. ICSE Workshop)

Teststufenspezifische Qualitätsattribute für die Qualitätsbewertung von nichtfunktionalen Anforderungen - Sancar, Yavuz; Brüseke, Frank; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Knowledge Transfer in Global Software Development - Leveraging Ontologies, Tools and Assessments - Salger, Frank; Sauer, Stefan; Engels, Gregor; Baumann, Andrea (5th IEEE International Conference on Global Software Engineering (ICGSE 2010))
To be successful with global software development (GSD), development knowledge needs to be shared among the developers and stakeholders, and the quality of the exchanged information must be assured. Therefore, mature processes, methods and tools have to be in place. If a unified and integrated solution does not exist, this impedes the exchange of knowledge (and the migration of people between projects). In GSD, such a diversity can lead to new problems: offshore development teams have to repeatedly re-adjust to method variants used by the respective business units. This can lead to misinterpretation of information and risks for project success. We report on re-aligning the varying software engineering methods and unifying the methodology throughout Capgemini sd&m. We also standardized quality assurance procedures and tightly integrated them with the engineering methodology. By this, we arrived at a comprehensive company-wide Enterprise Software Engineering Model that effectively supports knowledge transfer from clients to the onshore and offshore team.

MDDAUI 2010 Workshop Report - Van den Bergh, Jan; Meixner, Gerrit; Sauer, Stefan (Proc. 5th Intl. Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI 2010))

Pattern-based Generation of Test Plans for Open Distributed Processing Systems - Güldali, Baris; Sauer, Stefan; Winkelhane, Peter; Jahnich, Michael; Funke, Holger (Proceedings of 5th International Workshop on Automation of Software Test (AST 2010), ICSE Workshop)

Architecture-Driven Derivation of Performance Metrics - Brüseke, Frank; Sancar, Yavuz; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Effort Comparison of Model-based Testing Scenarios - Güldali, Baris; Mlynarski, Michael; Sancar, Yavuz (Proceedings of 3th International Conference on Software Testing, Verification, and Validation Workshops)

Test Case Generation for Visual Contracts Using AI Planning - Schnelte, Matthias; Güldali, Baris (INFORMATIK 2010, Beiträge der 40. Jahrestagung der Gesellschaft für Informatik e.V. (GI))

Ultrasonically-assisted Hydrothermal Method for Ferroelectric Material Synthesis - Ageba, Ryo; Kadota, Yoichi; Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Bornmann, Peter; Hemsel, Tobias (Journal of Korean Physical Society)
The hydrothermal method enables the production of high-quality piezoelectric materials. In this study, we propose to irradiate the reaction solutions with ultrasonic power during the hydrothermal method to obtain a shorter reaction time and a smooth film surface. A high-pressure reaction container for the ultrasonic transducer was newly developed, and the ultrasonically-assisted hydrothermal method was examined by using this container. The effect of ultrasonic assist on the synthesis of lead-zirconate-titanate (PZT) thin films and (K,Na)NbO$_{3}$ powders was verified. Thicker PZT film, thickness around 10 ${μ}$m, could be obtained in one process, and (K,Na)NbO$_{3}$ powder was synthesized in half the previous reaction time.
Keywords: Hydrothermal method; High-power ultrasonic; PZT thin film; Lead-free piezoelectric materials

Ultrasonic Transducer for the Hydrothermal Method - Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Ageba, Ryo; Kadota, Yoishi; Morita, Takeshi (Journal of Korean Physical Society)
Direct ultrasound irradiation is advantageous to increase the efficiency of the hydrothermal method which can be used for the production of piezoelectric thin films and lead free piezoelectric ceramics. To apply ultrasound directly to the process transducer prototypes were developed regarding the boundary conditions of the hydrothermal method. LiNbO$_{3}$ and PIC 181 were proven as feasible materials for high temperature resistant transducers ($≥ 200^° C$). Resistance of the transducers horn against the corrosive mineralizer was achieved by using Hastelloy C-22. The efficiency of the ultrasound assisted hydrothermal method depends on the generated sound field. Impedance and sound field measurements have shown that the sound field depends on the filling level and the position and design of the transducer.
Keywords: High-temperature transducer; Hydrothermal method; Lithium-niobate transducer

Modeling of Piezoelectric Langevin Transducers by Using Mixed Transfer Matrix Methods - Fu, Bo; Li, Chao; Zhang, Jianming; Huang, Zhenwei; Hemsel, Tobias (Journal of Korean Physical Society)
In the modeling of piezoelectric Langevin transducers using usual transfer matrix methods, some simplifications have been adopted. This leads to reduction of the model quality. A mixed transfer matrix method is employed in the modeling of Langevin transducers, where the pre-stressed bolt is modeled as a separate four-pole element, which is connected to other elements in parallel. Based on the mixed transfer matrix method, the four (six)-pole element description of the piezoelectric Langevin transducer is built up and the total transfer matrix relation is derived. The resonance frequencies of the transducer are calculated and then measured using the impedance analyzer (HP4192). Experimental result shows that the mixed transfer matrix method has better modeling quality than the usual transfer matrix method for the vibration analysis of piezoelectric Langevin transducers.
Keywords: Piezoelectric langevin transducer; Transfer matrix method; Four (six)-pole element description; Pre-stressed bolt

Reibungsdämpfung in ausgedehnten, verschraubten Fügestellen - Hölzl, Johannes Sebastian; Sextro, Walter (PAMM)
Bei der Konstruktion von Maschinen ist es oftmals erforderlich, Schwingungen minimal zu halten. Um z.B. die Lebensdauer zu erhöhen, Material einzusparen oder den Geräuschpegel gering zu halten muss oft ein großer Aufwand zur Dämpfung von auftretenden Schwingungen betrieben werden. In vielen technischen Anwendungen werden Einzelteile miteinander verschraubt. Diese Fügestellen können gezielt und mit wenig Aufwand zur Schwingungsdämpfung herangezogen werden. Die Berechnung des dynamischen Verhaltens verschraubter Strukturen stellt immer noch eine Herausforderung dar. Es wurde eine Methode entwickelt, um den eingeschwungenen Zustand elastischer, miteinander verschraubter Körper mit rauen Fügestellen bei periodischer Anregung zu berechnen. Als Basis dienen Finite Elemente Modelle der einzelnen Teile, deren Freiheitsgrade durch modale Kondensation reduziert werden. Unter Anwendung des Verfahrens von Ritz und Galerkin wird eine Näherungslösung für den eingeschwungenen Zustand des nichtlinearen, gekoppelten Systems ermittelt. Abhängig von den Schraubenvorspannkräften sowie den bestimmenden Parametern der Kontaktflächen, Rautiefe und Reibungskoeffizient, kann die Systemantwort berechnet und optimiert werden. Um die Berechnungsmethode zu verifizieren wurden Experimente durchgeführt. Der Vergleich zwischen Messung und Rechnung zeigt eine gute Übereinstimmung. ({©} 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)